Description of Students' Science Literacy Ability on Electrolyte and Non-Electrolyte Solution Materials at SMAN 11 Pontianak - Puspita, Ninda Ikke; Junanto, Tulus; Harun, Andi Ifriany; Enawaty, Eny; Ulfah, Maria (Universitas Pendidikan Mandalika, 2024)
It is important for students to learn scientific literacy because it’s related to how students understand the environment and face issues in modern society. Students with excellent scientific literacy skills are able to apply the concepts and facts learned at school in everyday situations. The purpose of this research is to provide an overview of students’ scientific literacy at SMA Negeri 11 Pontianak. The research method used is descriptive research with a quantitative approach. The population under study consists of grade XI science students, including XI IPA 1, XI IPA 2, and XI IPA 3. Sample selection employs purposive sampling technique, considering specific factors such as students who have received instruction from teachers in the subject of electrolyte solutions and possess a good academic abilities. A total of 37 students from class XI IPA 2 are chosen as research samples. Data collection technique involves measurement and communications, utilizing instruments in the form of five essay questions that have been tested for validity. Based on the research data, it is known that aspect of explaining scientific phenomena reached 60,47%, while in determine the properties and samples of solutions from electrical conductivity experimental data, percentage is 75%. To provide conclusions and opnions on electrolyte test results from everyday life phenomena reached 61,93%. If averaged, overall, students’ scientific literacy skills are in the moderate category, with an average score of 65,251%.